ANALISIS KINERJA MENGGUNAKAN PENDEKATAN BALANCED SCORECARD (PADA PT ARMADA INTERNATIONAL MOTOR) - Sari, Devi Novita; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTPerformance assessment method which can assess company performance accurately and holistically is required in dealing with the current complex business environment. Balance Scorecard is one of the methods which can be applied in this matter. Balance Scorecard is a performance assessment tool which combines financial non-financial performance standard. Measures the performance from four perspectives, i.e.: financial perspective, customer perspective, internal business perspective, and growth and learning perspective. Therefore, this research is meant to find out the performance of PT Armada International Motor Surabaya branch by using Balanced Scorecard method since PT Armada International Motor has not implemented the Balanced Scorecard method. The researcher applies qualitative research which is a non-hypothesis research, so a hypothesis is not necessary to be formulated. The data collection technique has been carried out by performing observation, interview, documentation, and questionnaires. The result of the research shows that financial perspective during three years experienced degression. Customer perspective in which during three years the company could not maintained their customer. The internal business process perspective shows that every year the company has performed innovation in order toi improve their product quality. The growth and learning perspective in which during three years the sales experienced degression.Keywords: Balanced Scorecard, financial perspective, customer perspective, internal business perspective, growth and learning perspective.